A comprehensive review of ethnomedicinal approaches, phytochemical analysis, and pharmacological potential of Vitex trifolia L. - Mottaghipisheh, Javad; Kamali, Marzie; Doustimotlagh, Amir Hossein; Nowroozzadeh, Mohammad Hossein; Rasekh, Fatemeh; Hashempur, Mohammad Hashem; Iraji, Aida (Frontiers in Pharmacology, 2024)
Plants, renowned for their rich reservoir of metabolites, play a pivotal role in addressing health-related issues. The Verbenaceae family stands out, showcasing immense potential in preventing and treating chronic diseases. Vitex trifolia L. (V. trifolia), a shrub with a rich history in traditional medicine, particularly in Eastern Asia, has garnered attention for its diverse therapeutic applications. This comprehensive review aims to bridge traditional knowledge and contemporary insights by investigating ethnopharmacology, phytochemistry, and pharmacological effects of V. trifolia.The keyword ' V. trifolia ' and its synonyms were searched within the main scientific databases including